PENGARUH CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE TERHADAP PROFITABILITAS PERUSAHAAN SEKTOR ENERGI INDONESIA SHARIA STOCK INDEX 2021-2022 - Rofiq Achmad Rozaan; -, Dwi Retno Widiyanti (Islamic Economics and finance in Focus, 2024)
This article aims to determine the effect of corporate social responsibility on the profitability of energy sector companies registered with ISSI for the 2021-2022 period. This research uses a descriptive quantitative approach to find the effect of CSRD on profitability as measured using Return on Equity (ROE) with leverage and liquidity control variables by conducting a Least Square based panel data linear regression test. The results of the analysis show that CSRD has a significant positive effect on ROE, while Leverage (Debt to Equity Ratio) has no effect on ROE and liquidity (Current Ratio) has a negative effect on ROE. Keywords: Corporate Social Responsibility Disclosure, Corporate Social Responsibility, Profitability, Leverage, Liquidity.